2019
DOI: 10.1590/1980-549720190060
|View full text |Cite
|
Sign up to set email alerts
|

Recebimento de aconselhamento nutricional por adultos e idosos em um município do Sul do Brasil: estudo de base populacional

Abstract: RESUMO: Introdução: O aconselhamento nutricional vem desempenhando um papel de suma importância na prevenção e no tratamento de diversas doenças. Objetivo: Avaliar o recebimento de aconselhamento nutricional em adultos e idosos residentes na área urbana de um município do Sul do Brasil. Métodos: Estudo transversal de base populacional. Os dados foram coletados através de questionário aplicado em domicílio. O desfecho foi o recebimento de aconselhamento nutricional no último ano vinculado a diversos meios… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
6
0
2
Order By: Relevance
“…We considered the following indicators : household being registered in the FHS program; a community health worker visit in the previous 12 months; having a health insurance plan; medical consultation in the previous 12 months; dental consultation in the previous six months; dietary counseling in the previous year 14 ; class with a physical education professional in the previous three months 15 ; flu vaccine in the previous 12 months; mammography exam and cytopathological exams (for women); and prostate exam (for men).…”
Section: Methodsmentioning
confidence: 99%
“…We considered the following indicators : household being registered in the FHS program; a community health worker visit in the previous 12 months; having a health insurance plan; medical consultation in the previous 12 months; dental consultation in the previous six months; dietary counseling in the previous year 14 ; class with a physical education professional in the previous three months 15 ; flu vaccine in the previous 12 months; mammography exam and cytopathological exams (for women); and prostate exam (for men).…”
Section: Methodsmentioning
confidence: 99%
“…Studies about the management of individuals with hypertension and diabetes have shown a low prevalence of receiving advice on healthy habits. These populations were expected to have greater attention from health professionals with good standard recommendations 8,19,20 . In addition, the distribution of advice varies according to sociodemographic and economic characteristics, with higher prevalence among those with white skin color, higher economic and schooling levels 8,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data from a meta-analysis published in 2018 showed significant reductions in body mass and body fat in premenopausal and postmenopausal women after nutritional and physical interventions (68). Therefore, for the success of a weight loss program, it is necessary to prescribe food or nutritional guidance (10)(11)(12)(13), as well as the incorporation of physical exercises, especially strength exercises, to maintain or increase muscle mass.…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been used to minimize the impacts caused by obesity. Among these, lifestyle interventions that combine changes in eating behavior and regular exercise should be incorporated as a first step by those seeking weight loss (8)(9)(10)(11)(12)(13)(14). Current guidelines advocate the need for lifestyle changes, but calorie-restricted diets and/or macronutrient-manipulated diets continue to be the most widely used method to promote weight reduction and prevent CVD (9,15).…”
Section: Introductionmentioning
confidence: 99%